Locating People Diagnosed With HIV for Public Health Action: Utility of HIV Case Surveillance and Other Data Sources. (March 2018) - Padilla, Mabel; Mattson, Christine L.; Scheer, Susan; Udeagu, Chi-Chi N.; Buskin, Susan E.; Hughes, Alison J.; Jaenicke, Thomas; Wohl, Amy Rock; Prejean, Joseph; Wei, Stanley C.
Introduction: Human immunodeficiency virus (HIV) case surveillance and other health care databases are increasingly being used for public health action, which has the potential to optimize the health outcomes of people living with HIV (PLWH). However, often PLWH cannot be located based on the contact information available in these data sources. We assessed the accuracy of contact information for PLWH in HIV case surveillance and additional data sources and whether time since diagnosis was associated with accurate contact information in HIV case surveillance and successful contact. Materials and Methods: The Case Surveillance-Based Sampling (CSBS) project was a pilot HIV surveillance system that selected a random population-based sample of people diagnosed with HIV from HIV case surveillance registries in 5 state and metropolitan areas. From November 2012 through June 2014, CSBS staff members attempted to locate and interview 1800 sampled people and used 22 data sources to search for contact information. Results: Among 1063 contacted PLWH, HIV case surveillance data provided accurate telephone number, address, or HIV care facility information for 239 (22%), 412 (39%), and 827 (78%) sampled people, respectively. CSBS staff members used additional data sources, such as support services and commercial people-search databases, to locate and contact PLWH with insufficient contact information in HIV case surveillance. PLWH diagnosed <1 year ago were more likely to have accurate contact information in HIV case surveillance than were PLWH diagnosed ≥1 year ago ( P = .002), and the benefit from using additional data sources was greater for PLWH with more longstanding HIV infection ( P < .001). Practice Implications: When HIV case surveillance cannot provide accurate contact information, health departments can prioritize searching additional data sources, especially for people with more longstanding HIV infection.